Use of alpha-tricalcium phosphate bone cement in the surgical treatment of mastoid cavity - Brito Neto, Rubens Vuono de (International Archives of Otorhinolaryngology, 2008)
Introduction: Open cavity mastoidectomy can generate some complications and mastoid cavity obliteration is a technique described and studied for the elimination of this cavity. Alloplastic materials have been studied in mastoid cavity obliteration surgery. Alpha-tricalcium phosphate bone cement is a material composed by calcium and phosphate and presents biochemical characteristics similar to the bone mineral phase. Objective: This study is aimed at evaluating the biocompatibility of alpha-tricalcium phosphate bone cement in the obliteration of the mastoid cavity in guinea pigs. Methods: 20 guinea pigs were submitted to surgical procedure. In 10 cement study group animals, the tympanic bulla was obliterated with alpha-tricalcium phosphate bone cement and in 10 guinea pigs (control group), the cavity was left unfilled. The animals were evaluated for clinical signs of material rejection and other complications. The temporal bones were removed and analyzed as for the type and degree of inflammatory response, as well as the degree of ossification. Results: In the animals that completed the study, there were no complications. There were not either the presence of foreign body inflammatory reaction in none of the samples of both groups. As for the ossification degree, the average ossification scores in the control group (3.5) was greater than that shown by the cement group (1.0). Conclusions: 1) The alpha-tricalcium phosphate bone cement is biocompatible in guinea pig's temporal bone 2) The alphatricalcium phosphate bone cement undergoes bone remodeling, but it doesn´t present osteoconductive properties.